Characterization of phenolic compounds from Eugenia supra-axillaris leaf extract using HPLC-PDA-MS/MS and its antioxidant, anti-inflammatory, antipyretic and pain killing activities in vivo - Hegazi, Nesrine M.; Sobeh, Mansour; Rezq, Samar; El-Raey, Mohamed A.; Dmirieh, Malak; El-Shazly, Assem M.; Mahmoud, Mona F.; Wink, Michael (Scientific reports, 2019)
Reactive oxygen species (ROS) are involved in the pathophysiology of several health disorders, among others inflammation. Polyphenols may modulate ROS related disorders. In this work, thirty-two phenolic compounds were tentatively identified in a leaf extract from Eugenia supra-axillaris Spring. ex Mart. using HPLC-MS/MS, five of which were also individually isolated and identified. The extract displayed a substantial in vitro antioxidant potential and was capable of decreasing ROS production and hsp-16.2 expression under oxidative stress conditions in vivo in the Caenorhabditis elegans model. Also, the extract showed higher inhibitory selectivity towards COX-2 than COX-1 in vitro with higher selectivity towards COX-2 than that of diclofenac. The extract also exhibited anti-inflammatory properties: It attenuated the edema thickness in a dose dependent fashion in carrageenan-induced hind-paw odema in rats. In addition, the extract reduced the carrageenan-induced leukocyte migration into the peritoneal cavity at the highest dose. Furthermore, the extract showed antipyretic and analgesic activities in a mouse model. Eugenia supra-axillaris appears to be a promising candidate in treating inflammation, pain and related oxidative stress diseases.
Gesehen am 22.10.2019